2018
DOI: 10.1111/bjh.15685
|View full text |Cite
|
Sign up to set email alerts
|

Impact of graft‐versus‐lymphoma effect on outcomes after reduced intensity conditioned‐alemtuzumab allogeneic haematopoietic stem cell transplantation for patients with mature lymphoid malignancies

Abstract: Summary Allogeneic haematopoietic stem cell transplant (allo‐HSCT) offers potentially curative therapy for patients with relapsed/refractory lymphoid malignancies. Reduced‐intensity conditioning (RIC) with Alemtuzumab reduces transplant‐related mortality and graft‐versus‐host disease (GvHD), but may be associated with increased risk of relapse. With the aim of studying the effect of GVHD and donor lymphocyte infusions (DLI) on relapse, we performed a retrospective study of 288 patients (57% non‐Hodgkin lymphom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…Nevertheless chimerism monitoring, post RIC allo-SCT is an important way of identifying patients at high risk of relapse in whom intervention with pre-emptive DLI may be beneficial. Patients who achieve full donor chimerism (FDC) with DLI have a comparable outcome to those who reach FDC spontaneously ( 148 , 149 ).…”
Section: How Should Patients With Aml In Cr1 Be Transplanted?mentioning
confidence: 99%
“…Nevertheless chimerism monitoring, post RIC allo-SCT is an important way of identifying patients at high risk of relapse in whom intervention with pre-emptive DLI may be beneficial. Patients who achieve full donor chimerism (FDC) with DLI have a comparable outcome to those who reach FDC spontaneously ( 148 , 149 ).…”
Section: How Should Patients With Aml In Cr1 Be Transplanted?mentioning
confidence: 99%
“…The addition of rituximab to augment the effects of DLI has been evaluated in two studies with conflicting results; in one report, 20/43 (47%) patients achieved complete responses which tended to be durable, whereas in the second study a sustained remission was achieved in only 2/13 (15%) patients (148,153). The potential benefit of DLI must also be weighed against the substantial risks of inducing clinically significant GVHD in up to 38-48% of patients (148,153,154). BTK and BCL2 inhibitors represent other highly effective treatment options for patients relapsing after allogeneic HCT who have not previously developed resistance to these therapies (155)(156)(157)(158).…”
Section: Monitoring and Management Of Disease Relapse After Allogenei...mentioning
confidence: 99%
“…AlloHSCT is also associated with significant toxicities, including graft-versus-host disease (GVHD), which could increase non-relapse mortality risk. GVHD, and especially the chronic GVHD, has been shown to be associated with lower risk of relapse, which may reflect the benefits of graft-mediated immune surveillance in the prevention of lymphoma relapse [10,29]. Given the lack of randomized prospective trials evaluating the role of AlloHSCT in cHL, multiple retrospective, small prospective phase 2 and registry studies have shown the benefit of this procedure in selected fit patients with relapsed disease [30].…”
Section: Role Of Allogeneic Hsct In Relapsed/refractory Hlmentioning
confidence: 99%
“…More than a decade of progress has made this modality safer and accessible to more patients worldwide [7]. The benefits of AlloHSCT go beyond the anticancer effects of high-dose chemotherapy and radiotherapy, to the more durable graft-versus-lymphoma phenomenon [8][9][10]. Furthermore, the recognition of the benefits of graft-versus-lymphoma effects has allowed clinicians to use lower doses of chemo-or radiotherapy (reduced-intensity conditioning, RIC) with a reduction in toxicity while achieving good outcomes.…”
Section: Introductionmentioning
confidence: 99%